Method for rapidly detecting influence of different sand molds on thermal storage stability of real stone paint and application thereof
By using high-speed stirring and disperser in real stone paint, the thermal storage stability problem of real stone paint is solved, production efficiency and product quality are improved, and testing time and cost are reduced.
Patent Information
- Application Number
- CN202310842869.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-14
AI Technical Summary
In the real stone paint industry, the difference in water absorption and specific surface area of different sand types leads to thermal storage stability issues, affecting production efficiency and product quality, and the traditional method takes time to detect and affecting the lead time.
The rapid detection method is adopted, by adding different sand types or wetting dispersants to the real stone paint, dispersing with high-speed stirring and disperser, recording viscosity and agglomeration phenomena, quickly assessing the stability of heat storage, and reducing material loss and detection time.
It realizes rapid and convenient detection of the impact of different sand types on the thermal storage stability of real stone paint and screening of wetting dispersants, improves work efficiency, reduces measurement costs and time, and ensures product quality.
Smart Images

Figure SMS_1 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the testing field of water-based coatings, and in particular to a method for rapidly detecting the influence of different sand types on the thermal storage stability of real stone paint and an application of the method in screening a wetting dispersant for improving the post-thickness of real stone paint. Background Art
[0002] Real stone paint is a kind of paint with decorative effect similar to marble and granite. It is mainly made of natural stone powder of various colors and applied to the imitation stone effect of building exterior walls, so it is also called liquid stone. Buildings decorated with real stone paint have natural and real natural color, giving people an elegant and solemn beauty. It is suitable for indoor and outdoor decoration of various buildings, especially for decoration on curved buildings. It is vivid and lifelike, with a return to nature effect.
[0003] In the real stone paint industry, different types of sand are often used for skeleton proportioning at work. However, since mineral resources are affected by environmental factors, although natural stone powder can artificially control the particle size of the sand mold, the internal structure of the ore is affected by the environment of the mine mountain range, and there are differences between batches of specific surface area and water absorption. If the same sand mold changes due to ore vein changes, there will be differences in water absorption and specific surface area. When preparing real stone paint, sand molds with large specific surface area and large water absorption will affect the thermal storage stability of the real stone paint, causing the real stone paint to thicken or even agglomerate, affecting the construction performance. Even if the same supplier and the same type of sand mold have different batches, the water absorption and specific surface area will be different. This difference has a greater impact on the thermal storage stability. For example, in 2019, the white marble sand mold (80-120 mesh) provided by the same supplier appeared. The specific surface area and water absorption of different product batches were quite different, resulting in the real stone paint produced using the white marble sand mold being delivered to the customer site. Within one month, it became thick and agglomerated and could not be used, causing large-scale complaints and bringing huge economic losses to the company. Before using the sand molds in production, laboratory tests are carried out to determine the appropriate proportions. Thermal storage stability is one of the items that needs to be tested. If the demand for sand molds is large and the test time is too long, it will affect production efficiency and delivery cycle.
[0004] In addition, during the product test of real stone paint, the real stone paint showed the phenomenon of post-thickening and clumping, and the product formula needed to be adjusted. Experimental research showed that adding a wetting and dispersing agent could improve the post-thickening and clumping, but it required tedious construction and heat storage tests on each wetting and dispersing agent paint sample in order to compare the differences in the improvement effects of different wetting and dispersing agents, which was time-consuming and labor-intensive. Summary of the invention
[0005] In order to solve the technical problems such as the long time consumption in detecting the thermal storage stability in the traditional method, the technical problem to be solved by the present invention is to provide a method for quickly detecting the influence of different sand types on the thermal storage stability of real stone paint and its application in the screening of wetting dispersants to improve the post-thickness of real stone paint.
[0006] By using the method of the present invention for rapidly detecting the influence of different sand molds on the thermal storage stability of real stone paint, the thermal storage stabilities of different types of sand molds in real stone paint can be rapidly compared, thereby rapidly evaluating whether the sand mold is usable, and material loss is low.
[0007] When the present invention is used in the screening of wetting and dispersing agents for improving the post-thickness of real stone paint, no construction and heat storage tests are required in the screening of different wetting and dispersing agents, and whether the heat storage stability in the experiment of improving the post-thickness of real stone paint is qualified can be quickly detected.
[0008] To solve the above problems, the present invention is implemented through the following technical solutions:
[0009] The first object of the present invention is:
[0010] A method for quickly detecting the influence of different sand types on the thermal storage stability of real stone paint is provided, which comprises the following steps:
[0011] S1. Make a BASE paint sample of real stone paint without screening sand mold;
[0012] The said real stone paint BASE paint sample means that except for the selected sand mold, all other components have been added according to the formula ratio;
[0013] S2. The real stone paint BASE paint sample is divided into several equal weight portions for standby use, each portion is added with different types of sand to be screened to obtain the corresponding real stone paint sample containing the screened sand type;
[0014] The different types of sand that need to be screened are added in the same proportion and with the same weight;
[0015] S3. The corresponding real stone paint sample containing the screened sand mold obtained in step S2 is dispersed at the following stirring speed and stirring time to achieve the effect of destroying the sand mold:
[0016] Stirring speed: 1000±20 rpm;
[0017] Stirring time: 30 minutes;
[0018] Record the viscosity of each real stone paint sample and whether it is unable to stir and has lumps.
[0019] The method of the present invention for rapidly detecting the influence of different sand types on the thermal storage stability of real stone paint is further optimized as follows:
[0020] After dispersion, if the viscosity increases and the agglomeration cannot be stirred, the corresponding real stone paint sample fails the thermal storage stability test;
[0021] After dispersion, if there is no obvious increase in viscosity and no agglomeration, the corresponding real stone paint sample passes the thermal storage stability test.
[0022] The method of the present invention for rapidly detecting the influence of different sand types on the thermal storage stability of real stone paint is further optimized as follows:
[0023] The dispersion in step S3 is performed using a three-blade disperser.
[0024] The method of the present invention for rapidly detecting the influence of different sand types on the thermal storage stability of real stone paint is further optimized as follows:
[0025] The dispersion in step S3 is performed using a Tianjin Senrida QSJ disperser, and the three-blade paddle dispersion diameter is 50 mm.
[0026] The method of the present invention for rapidly detecting the influence of different sand types on the thermal storage stability of real stone paint is further optimized as follows:
[0027] In the step S3, the test temperature of the viscosity of the real stone paint sample is controlled at 25° C., using a VT-06 viscometer.
[0028] In the method for quickly detecting the influence of different sand types on the thermal storage stability of real stone paint of the present invention, the dispersion speed is 1000±20 rpm and the dispersion time is 30 minutes. Compared with the conventional real stone paint dispersion speed of 400-600 rpm and the dispersion time of 10-15 minutes, the rotation speed is increased and the time is extended. The high-speed friction achieves the effect of destroying the sand type, and can make the sand with large specific surface area react and agglomerate. This reaction effect is consistent with the effect of agglomeration and coagulation after thermal storage for 15 days, and the influence of different sand types on the thermal storage stability of real stone paint can be quickly detected.
[0029] Compared with the prior art, the method of the present invention only takes a short time to quickly and conveniently detect the effects of different sand types on the thermal storage stability of real stone paint.
[0030] The second object of the present invention is:
[0031] A method for quickly detecting the effect of different wetting and dispersing agents on the post-viscosity of real stone paint is provided, which comprises the following steps:
[0032] s1. Make a real stone paint sample without screening wetting and dispersing agent;
[0033] The real stone paint sample refers to the paint sample in which all components except the selected wetting and dispersing agent have been added according to the formula ratio;
[0034] s2. The real stone paint sample is divided into several equal portions by weight for standby use, each adding a different wetting and dispersing agent of the required screening model to obtain the corresponding complete real stone paint sample containing the screening wetting and dispersing agent;
[0035] The different types of sand that need to be screened are added in the same proportion and with the same weight;
[0036] s3. The corresponding complete real stone paint sample containing the screened wetting and dispersing agent obtained in step s2 is dispersed at the following stirring speed and stirring time to achieve the effect of destroying the sand mold:
[0037] Stirring speed: 1000±20 rpm;
[0038] Stirring time: 30 minutes;
[0039] Record the viscosity of each complete real stone paint sample and whether it is unable to stir and agglomerate.
[0040] The method of the present invention for rapidly detecting the effect of different wetting and dispersing agents on the post-viscosity of real stone paint is further optimized as follows:
[0041] After dispersion, if the viscosity increases and the agglomeration cannot be stirred, the corresponding improved viscosity effect of the complete real stone paint sample is not acceptable;
[0042] After dispersion, there is no obvious increase in viscosity and no agglomeration phenomenon, and the corresponding complete real stone paint sample has a good improvement in viscosity.
[0043] The method of the present invention for rapidly detecting the effect of different wetting and dispersing agents on the post-viscosity of real stone paint is further optimized as follows:
[0044] The dispersion in step s3 is carried out using a three-blade disperser.
[0045] The method of the present invention for rapidly detecting the effect of different wetting and dispersing agents on the post-viscosity of real stone paint is further optimized as follows:
[0046] The dispersion in step s3 is performed using a Tianjin Senrida QSJ disperser, and the three-blade pulp dispersion diameter is 50 mm.
[0047] The method of the present invention for rapidly detecting the effect of different wetting and dispersing agents on the post-viscosity of real stone paint is further optimized as follows:
[0048] In step s3, the test temperature of the viscosity of the complete real stone paint sample is controlled at 25°C.
[0049] A VT-06 viscometer was used.
[0050] The method for quickly detecting the effects of different wetting and dispersing agents on the post-viscosity of real stone paint of the present invention does not require construction and heat storage testing in the screening of different wetting and dispersing agents, and can quickly detect whether the heat storage stability in the experiment of improving the post-viscosity of real stone paint is qualified.
[0051] Therefore, when the post-viscosity of the real stone paint is agglomerated or there are problems with the construction during the test of the real stone paint product, and it is necessary to use additives to adjust the product to improve the construction effect, the method of the present invention for rapidly detecting the influence of different wetting and dispersing agents on the post-viscosity of the real stone paint can be used. Without the need for a cumbersome construction process, the difference in the improvement effect of different wetting and dispersing agents can be compared, which has the advantages of being convenient and fast, reducing product time consumption, and improving work efficiency. DETAILED DESCRIPTION
[0052] In order to make the application, technical scheme and advantages of the present invention clearer, the present invention is described in detail in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not limited to the present invention. All simple improvements to the preparation method of the present invention under the premise of the present invention are within the protection scope of the present invention.
[0053] Example 1
[0054] Prepare 16,000 grams of BASE paint sample of natural stone paint without screening sand (the remaining components are added according to the required formula ratio), and fill the BASE paint sample of natural stone paint into 15 1L plastic cans, with 1000.0 grams of paint sample in each can, accurate to 1 decimal place;
[0055] Add 1 to 5 samples of the same type of sand from 5 different manufacturers, each of which is a group of 3 1L plastic cans. Add the same type of sand, a total of 15 paint samples. The amount of sand added is added according to the formula ratio, and the amount added is the same, accurate to 1 decimal place, to obtain real stone paint samples;
[0056] Use Tianjin Senrida QSJ disperser to disperse the real stone paint samples with sand added, with a three-blade slurry of 50 mm in diameter; the paint samples are grouped into three 1L plastic cans, respectively:
[0057] Speed 600 rpm (normal speed), dispersion for 15 minutes;
[0058] Speed 800 rpm, dispersion for 30 minutes;
[0059] Speed 1000 rpm, dispersion 30 minutes;
[0060] After the three speeds of dispersion are completed, record the viscosity of each paint sample and whether it is difficult to stir or agglomerate;
[0061] The paint samples were subjected to a 15-day hot storage test at a normal speed of 600 rpm and dispersion for 15 minutes. After 15 days, the viscosity and whether there was a phenomenon of agglomeration that could not be stirred were recorded. The measurement results of 5 different sand-type real stone paint samples are shown in Table 1.
[0062] 15d hot storage test: conduct a hot storage experiment according to the hot storage stability (15d) required by the standard JG / T 24-2018 for real stone paint products. After 15 days, record the viscosity and whether there is any inability to stir or agglomerate.
[0063] Table 1 Measurement results of different sand type real stone paint samples 1 to 5
[0064]
[0065] It can be seen from Table 1 that among the measurement results of the above 5 different sand-type real stone paint samples, the thermal storage stability data results of normal rotation speed dispersion are: sample 3 and sample 5 are agglomerated, and the other samples 1, sample 2, and sample 4 are not agglomerated; the paint sample results of dispersion at a rotation speed of 1000±20 rpm for 30 minutes are: sample 3 and sample 5 are agglomerated, and the other samples 1, sample 2, and sample 4 are not agglomerated, and the results of the two are consistent.
[0066] By comparison, the conclusions obtained by comparing the thermal storage stability effects of the same sand-type real stone paint samples using the method of the present invention and the traditional method are the same, but the measurement time of the method of the present invention is much shorter than that of the traditional method. This shows that the method of the present invention not only improves work efficiency, but also greatly saves measurement costs.
[0067] Example 2
[0068] Prepare 11000g of hot storage thickened agglomerated real stone paint sample without screening aid, and fill the real stone paint sample into 10 1L plastic cans, with 1000.0g of paint sample in each can, accurate to 1 decimal place;
[0069] Add 5 different water-based paint wetting and dispersing agent samples 1 to 5 respectively, and add the same water-based paint wetting and dispersing agent to each 2 1L plastic cans as a group, for a total of 10 wetting and dispersing agent paint samples, and the amount of wetting and dispersing agent added is 0.50 grams, accurate to two decimal places;
[0070] The paint samples with the added wetting agent were dispersed by Tianjin Senrida QSJ type disperser, with a three-blade diameter of 50 mm and two 1L plastic cans as a group. The dispersion was completed at two speeds, 600 rpm for 15 minutes and 1000 rpm for 30 minutes.
[0071] Record the viscosity of each paint sample and whether it is difficult to stir or has lumps;
[0072] The paint samples were subjected to a 15-day hot storage test at a normal speed of 600 rpm and dispersion for 15 minutes. After 15 days, the viscosity and whether there was a phenomenon of agglomeration that could not be stirred were recorded. The measurement results of 5 different water-based paint wetting and dispersing agent samples are shown in Table 2.
[0073] 15d hot storage test: conduct a hot storage experiment according to the hot storage stability (15d) required by the standard JG / T 24-2018 for real stone paint products. After 15 days, record the viscosity and whether there is any inability to stir or agglomerate.
[0074] Table 2 Measurement results of wetting and dispersing agent samples 1 to 5 for water-based paint
[0075]
[0076]
[0077] As can be seen from Table 2, the viscosity improvement effects of the above five water-based paint wetting and dispersing agent samples after dispersion at a rotation speed of 1000±20 rpm for 30 minutes are as follows: Sample 1, Sample 5, Sample 4, Sample 2, Sample 3. Among them, Sample 3 has the best viscosity improvement effect, which is consistent with the thermal storage stability results of dispersion at normal rotation speed.
[0078] In the process of comparing the viscosity improvement effects of various water-based paint wetting and dispersing agent samples, the conclusions obtained by comparing the viscosity improvement effects by the method of the present invention and the traditional method are the same, but the measurement time by the method of the present invention is much shorter than that by the traditional method, and the energy loss of electric energy and the like in the method of the present invention is also much smaller than that in the traditional method. It can be seen that the method of the present invention not only improves the work efficiency, but also greatly saves the measurement cost.
[0079] To sum up, the embodiments of the present invention are only preferred examples of the present invention and do not limit the present invention in any form. Any equivalent changes made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the disclosed technical content are regarded as equivalent examples of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
[0080] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0081] The experimental methods without specific conditions in the present invention are usually carried out under conventional conditions or conditions recommended by the manufacturer.
[0082] Unless otherwise stated, the various optimization technical solutions in the present invention can be combined with each other.
[0083] Unless otherwise indicated, percentages and parts are by weight.
[0084] Experimental methods without specific conditions specified in the instructions and examples are usually carried out under conventional conditions or conditions recommended by the manufacturers.
[0085] Unless otherwise defined, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention.
Claims
1. A method for quickly detecting the influence of different sand types on the thermal storage stability of real stone paint, characterized in that: It includes the following steps: S1. Make a BASE paint sample of real stone paint without screening sand mold; The said real stone paint BASE paint sample means that except for the selected sand mold, all other components have been added according to the formula ratio; S2. The real stone paint BASE paint sample is divided into several equal weight portions for standby use, each portion is added with different types of sand to be screened to obtain the corresponding real stone paint sample containing the screened sand type; The different types of sand that need to be screened are added in the same proportion and with the same weight; S3. The corresponding real stone paint sample containing the screened sand mold obtained in step S2 is dispersed at the following stirring speed and stirring time to achieve the effect of destroying the sand mold: Stirring speed: 1000±20 rpm; Stirring time: 30 minutes; Record the viscosity of each real stone paint sample and whether it is unable to stir and has lumps.
2. The method for rapidly detecting the influence of different sand types on the thermal storage stability of real stone paint according to claim 1, characterized in that: After dispersion, if the viscosity increases and the agglomeration cannot be stirred, the corresponding real stone paint sample fails the thermal storage stability test; After dispersion, if there is no obvious increase in viscosity and no agglomeration, the corresponding real stone paint sample passes the thermal storage stability test.
3. The method for rapidly detecting the influence of different sand types on the thermal storage stability of real stone paint according to claim 1, characterized in that: The dispersion in step S3 is performed using a three-blade disperser.
4. The method for rapidly detecting the influence of different sand types on the thermal storage stability of real stone paint according to claim 3, characterized in that: The dispersion in step S3 is performed using a Tianjin Senrida QSJ disperser, and the three-blade paddle dispersion diameter is 50 mm.
5. The method for rapidly detecting the influence of different sand types on the thermal storage stability of real stone paint according to claim 1, characterized in that: In the step S3, the test temperature of the viscosity of the real stone paint sample is controlled at 25° C., using a VT-06 viscometer.
6. A method for quickly detecting the effect of different wetting and dispersing agents on the post-viscosity of real stone paint, characterized in that: It includes the following steps: s1. Make a real stone paint sample without screening wetting and dispersing agent; The real stone paint sample refers to the paint sample in which all components except the selected wetting and dispersing agent have been added according to the formula ratio; s2. The real stone paint sample is divided into several equal portions by weight for standby use, each adding a different wetting and dispersing agent of the required screening model to obtain the corresponding complete real stone paint sample containing the screening wetting and dispersing agent; The different types of sand that need to be screened are added in the same amount and in the same weight; s3. The corresponding complete real stone paint sample containing the screened wetting and dispersing agent obtained in step s2 is dispersed at the following stirring speed and stirring time to achieve the effect of destroying the sand mold: Stirring speed: 1000±20 rpm; Stirring time: 30 minutes; Record the viscosity of each complete real stone paint sample and whether it is unable to stir and agglomerate.
7. The method for rapidly detecting the effect of different wetting and dispersing agents on the post-viscosity of real stone paint according to claim 6, characterized in that: After dispersion, if the viscosity increases and the agglomeration cannot be stirred, the corresponding improved viscosity effect of the complete real stone paint sample is not acceptable; After dispersion, there is no obvious increase in viscosity and no agglomeration phenomenon, and the corresponding complete real stone paint sample has a good improvement in viscosity.
8. The method for rapidly detecting the effect of different wetting and dispersing agents on the post-viscosity of real stone paint according to claim 6, characterized in that: The dispersion in step s3 is carried out using a three-blade disperser.
9. The method for rapidly detecting the effect of different wetting and dispersing agents on the post-viscosity of real stone paint according to claim 8, characterized in that: The dispersion in step s3 is performed using a Tianjin Senrida QSJ disperser, and the three-blade pulp dispersion diameter is 50 mm.
10. The method for rapidly detecting the effect of different wetting and dispersing agents on the post-viscosity of real stone paint according to claim 6, characterized in that: In the step s3, the test temperature of the viscosity of the complete real stone paint sample is controlled at 25° C., using a VT-06 viscometer.